Movimento Escola sem Partido e seus possíveis impactos no ensino de Filosofia - Miranda, Sitônio Coelho (2021)
This dissertation reflects on the impacts of the Movimento Escola sem Partido on education, in general, and on the teaching of philosophy, in particular. Such reflection is articulated from the concepts of culture, semi-culture and semi-formation, as well as the collapse of cultural formation in the modern world. It also brings a debate about ideology and its close relationship with school education, especially when it directly permeates the educational system, using the school to determine the maintenance of dominant ideas. The theoretical framework of the research is the German philosopher Theodor Adorno, who develops a thought based on “Education for emancipation”, whose objective is to prevent the repetition of Auschwitz, that is, to stop the human coldness, the indifference present in each one. Thus, in the light of his thinking, education will be understood as a promoter of autonomy and emancipation and, therefore, resistance. Based on this, we arrive at some ideas about the impacts of authoritarian, conservative ideas on philosophy teaching. Immersed in subculture and unable to recognize his alienated and minor condition, man needs an education by values. Some setbacks are faced by public school students and teachers. The permanence of philosophy in Brazilian Basic Education curricula, exclusively after the process of mass education, is also an act of resistance. The totalitarian elements and risks present in a school reduced to instruction have directly affected the teaching of philosophy in Brazilian basic education.